(3efGgd GdUaG aj JNQjL CMGOjK GdTaGs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3gPG cJGH fajS hVYJg hNQLJ ajg CMGOjK GdTaG ddbGVi YjGV SGdcG ajg WQjbG ehLRG eNJUQG s
(3BNQgG (B:s
(3Je GdcJGH hGddg GdgGOi ddUhGH s
(3Vef eLehY , JQJjHgG (B: 14s
(3YdjgG hba ddLGeY GdCYXe GdecJHI GdCMeOjI HJhfS HJGQjN (B1256 (3g`s
(3hQO HgOjI GdYGQajf (B543/1: (3efGgL GdUaGs
(3HjfeG ai cTa GdXfhf(B: (3efGgd ceG gh eKHJ s
(3JHUQI GdYfhGf (B:s
(3JNQjL s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs